2009
DOI: 10.1111/j.1475-4762.2008.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge–space dynamic in the UK bioeconomy

Abstract: The loss of manufacturing employment to lower cost economies has meant that countries like the UK have sought to promote innovation in areas such as biotechnology. The emergence of the 'bioeconomy', however, has been highly uneven, with concentrations of activity in certain countries and particular regions in those countries. In the UK, for example, there are four major concentrations of the bioeconomy. Each of these concentrations exhibit distinct patterns of knowledge and spatial inputs into the innovation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 54 publications
(59 reference statements)
0
9
0
2
Order By: Relevance
“…As a consequence, the conceptual development of the bio-economy has been driven by the fossil fuel substitution perspective, as well as the biotechnology innovations perspective, leading to multiple definitions for the bio-economy (see [6,7]). While early publications adopted sector specific definitions or focused purely on biotechnology [8,9], the bio-economy is increasingly being understood to include all kinds of economic activity that rely on biological processes, products, and principles [10]. In this study we adopt a broad definition that includes traditionally bio-based sectors such as agriculture and forestry, but also bio-based pharmaceutics, waste treatment, energy, bio-plastics, and chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the conceptual development of the bio-economy has been driven by the fossil fuel substitution perspective, as well as the biotechnology innovations perspective, leading to multiple definitions for the bio-economy (see [6,7]). While early publications adopted sector specific definitions or focused purely on biotechnology [8,9], the bio-economy is increasingly being understood to include all kinds of economic activity that rely on biological processes, products, and principles [10]. In this study we adopt a broad definition that includes traditionally bio-based sectors such as agriculture and forestry, but also bio-based pharmaceutics, waste treatment, energy, bio-plastics, and chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Also regions specialised in high-quality public research related to bio-technology may benefit in developmental terms [41]. It is furthermore suggested that connections between these global bio-technology centres are very important for innovation in the bioeconomy and that certain regions in emerging and developing economies may also take advantage of the bioeconomy [8,42].…”
Section: The Bio-technology Visionmentioning
confidence: 99%
“…Concomitantly, these attempts have also looked at the way value is created through the collection and use of such collections and their relation to economic development (Sunder Rajan, 2006;Waldby and Mitchell, 2006). Invariably, the production of scientific knowledge has been increasingly linked to forms of neoliberal governance and market operations (Birch, 2009) where information on the human body becomes an increasingly important commodity to control, own and exchange. The optimisation of these systems of collection and exchange also help to legitimise the high costs that have been invested in the collection of the samples and related information through public funding.…”
Section: Waste Discourse and Efficiencymentioning
confidence: 99%